Treating and Reducing Anxiety and Pain in the Paediatric Emergency Department (The Trapped 2 Survey): Time for Action – A Pediatric Emergency Research Canada (Perc) Project. (1st June 2016) - Trottier, ED; Gravel, J; Ali, S; Meckler, G; Blanchet, M; Stang, A; Porter, R; Lemay, S; Dubrovsky, A S; Chan, M; Jain, R; Principi, T; et al.
Abstract: BACKGROUND: Multiples barriers to appropriate analgesia provision are reported in the paediatric emergency department (PED), including limited accessibility to effective strategies. OBJECTIVES: To evaluate the improvement in the accessibility of pain and anxiety management strategies in PEDs in Canada, after the creation of a national pediatric pain quality improvement collaborative, through Pediatric Emergency Research Canada. DESIGN/METHODS: In 2013, the TRAPPED 1 survey was administered across Canadian PEDs, in order to evaluate the resources in place for pain and anxiety management. Subsequent to the TRAPPED 1, a pain Quality Improvement Collaborative was created to stimulate the implementation of new pain and anxiety management strategies through the sharing of information between PEDs. The TRAPPED 2 survey involved a cross sectional survey similar to TRAPPED 1, after a two year interval. Its main focus was to evaluate the improvement in the accessibility of specific, preferred strategies reported by each centre, after participating in this collaborative between December 2014 to November 2015, and then working to implement change within their own PEDs. RESULTS: All 15/15 Canadian PEDs responded to TRAPPED 1 in 2013. In 2014, 11/15 agreed to participate in the national pain Quality Improvement Collaborative, with a goal of introducing new pain and anxiety management strategies within their own PEDs. An in-person meeting, email communication, and telephone meetings were employed for information sharing regarding experiences/challenges within each of the participating centres. Newly introduced strategies included education, distraction, nurse-initiated protocols, and policies/education to encourage the use of intranasal (IN) medications. 11/11 centres have responded to the interim follow up surveys in 2015. At the end of the project (Fall 2105), 15/15 Canadian PEDs agreed to complete the final TRAPPED 2 survey. When comparing the results of 2015 with 2013, an increased number of PEDs used face-based pain scales (14/15 vs 6/15) and behavioural scales (5/15 vs 1/15) for pain assessment of school-aged children and infants, respectively. Use of assessment room wall decoration for distraction increased from 7/15 to 11/15. Reminder posters for pain management at triage increased from 4/15 to 6/15. Availability of electronic distraction strategies (e.g. using tablets) increased from 4/15 to 10/15 centres. For skin-piercing procedure, nurses initiated protocols to use topical anesthetic creams and oral sucrose was available in 12/15 centres (compared to 10/15 in 2013), and 14/15 (compared to 12/15 in 2013) respectively. Availability of IN medications increased in the last two years: fentanyl 14/15 (9/15 in 2013) and midazolam in at least 10/15 (8/15 in 2013). 10/11 PEDS involved in the QI strategy reported the implementation of at least one of their strategies identified. CONCLUSION: This study suggests that the use of a pain Quality Improvement Collaborative may improve the introduction of new strategies in multiple PEDs. It can help guide other centres when introducing new strategies to reduce pain and anxiety for children in community EDs. Future research can focus on the sustainability of the strategies, and as well the effect of the collaborative on the introduction of other pain treatment strategies.